Unveiling The Disability: A Study Of Social Discrimination In The Memoir - Being Heumann - Mian Muhammad Akram , Najia Asrar Zaidi (Migration Letters, 2024)
Memoires provide a better understanding of personal life as compared to the rest of fiction narratives and emerge as a true representative of individuals, especially when dealing with disabled persons in contemporary societies. Social discrimination often leads to stigmatization of disabled persons through negative attitude and behavior, thus paved a path towards formation of negative stereotypes, that adversely affects their socio-psychological domains. Such behavior can be traced in almost every memoire of a disabled person, even in advanced countries where disability rights have been exercised since decades. This paper aims[1] to highlight the social discrimination of disabled persons in contemporary American memoire, with special reference to “Being Heumann” by Judith Heumann (2020) through the lens of Dr Dana S Dun (2015). The study shows considerable depiction of social discrimination as discovered at various situations in the selected text. It ranges from social discrimination at home, school, workplace as well as at public places, as experienced by the disabled person. Moreover, it also sheds light on the steps to eliminate social discrimination of the disabled persons in the society by employing various technological gadgets, computer programs, software applications and above all by eliminating social and environmental barriers.